Cauda Equina Syndrome Clinical Guidelines Review - Shashikant Bhasme; Chishty , Qaiser Shahzad (International Journal of Endorsing Health Science Research, 2022)
In the wake of the COVID-19 pandemic, the national health services (NHS) had to adopt certain measures to amicably respond to the pandemic on the domestic front. Among these was the suspension of direct patient and physician interface to the extent possible, and the consultations were minimized to telecommunication. This review article aims to share the critical insights of current urgent care practice at the forefront of the advanced practice agenda that deals with complex issues both systematically and creatively, makes sound judgments in the absence of complete data, and communicates conclusions. Moreover, this review also highlights the originality in the application of knowledge, together with a practical understanding of local and national policy and drivers to support and develop an advanced practice that helps to critically evaluate current research and advanced scholarship in advanced practice.